PENGARUH KUALITAS LAYANAN, HARGA DAN CITRA MEREK TERHADAP KEPUASAN DAN LOYALITAS PELANGGAN POS EKSPRES DI KANTOR POS BONDOWOSO DAN SITUBONDO - Suwandi, Suwandi; Sularso, Andi; Suroso, Imam (Universitas Jember, 2015)
The objectives of this study was to determine the effect of service quality, price and brand image on Post Express customer satisfaction and loyalty in Bondowoso and Situbondo Post Office, using analytical methods Sructural Equation Modeling (SEM) with the of Amos program version 5.0. The population in this research is all customer who sent document or parcel with the Post Express service. The respondent are chosen by purposive sampling. This study uses primary data by taking a sample of customers Post Ekspres at the Bondowoso and Situbondo Post Office, as many as 133 samples. The results of this study are: (1) service quality has positive and significant impact on customer satisfaction; (2) price has positive and significant impact on customer satisfaction; (3) brand image has positive and significant impact on customer satisfaction, (4) customer service has positive and significant impact on customer loyalty; (5) price has positive and significant impact on customer loyalty; brand image has positive but not significant impact on customer loyalty; (7) satisfaction has positive and significant impact on customer loyalty. Keywords: service quality, price, brand image, satisfaction, customer loyalty